Resilience, coping strategies, and social support: important predictors of students' vulnerability to stress - Reza Davarniya; Mohammad Shakarami; Kianoush Zahrakar (Gonabad University of Medical Sciences, 2019)
Stress is a type of person-environment relationship which is appraised by the individual as stressful or beyond one's own resources and, as a results, threatens the individual's wellbeing and welfare. The aim of the present study was to investigate the variables of resilience, coping strategies, and social support as predictors of vulnerability to stress among students. The participants consisted of 375 university students who were selected by multistage cluster sampling method. The stress syndrome scale, checklist of coping skills, adult resilience inventory, and social support Appraisal scale were used to collect data. Data analysis was performed in SPSS-18 using simultaneous multiple regression analysis. Results suggested that the variables of resilience, social support, and coping strategies could predict 50.3% of the variance of vulnerability to stress. The variables of resilience, social support, and coping strategies can predict vulnerability to stress, and making changes in these factors can be effective in reducing vulnerability of people in face of stress.